PEMAHAMAN TERHADAP LITERASI KEUANGAN PADA MAHASISWA AKUNTANSI DAN NON-AKUNTANSI DI UNIVERSITAS WIDYA MANDIRA KUPANG - Bria, Philomena Yuniar Tuto; Manewalu, Cresensia Rianti; Fahik, Mariana; Lian, Yohanes P. (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study aims to explore the understanding of financial literacy among accounting and non-accounting students at the University of Widya Mandira (UNWIRA) Kupang using a qualitative approach. Financial literacy is an essential competency that supports individuals in making sound financial decisions, especially for students who are expected to manage their personal and professional finances responsibly. This research employed a descriptive qualitative method with data collected through in-depth interviews and observations. Participants consisted of students from accounting and non-accounting programs, selected through purposive sampling. The data were analyzed using thematic analysis to identify patterns and differences in financial literacy understanding between the two groups. The findings reveal that accounting students generally possess a better conceptual and practical understanding of financial literacy—particularly in budgeting, saving, and investment management—due to their academic exposure to finance-related courses. In contrast, non-accounting students tend to have a more limited understanding and focus mainly on basic aspects of personal finance management. However, both groups still show weaknesses in long-term financial planning and investment risk assessment. This study highlights the importance of integrating financial literacy education across all university programs to improve students’ financial competencies and better prepare them to face future economic challenges.